The Role of Spinal Cord Stimulation in Reducing Opioid Use in the Setting of Chronic Neuropathic Pain: A Systematic Review. Issue 4 (7th April 2022) - Smith, Cynthia A.; Roman, Jessica; Mammis, Antonios
Abstract : Objective: The aim was to examine research on the impact of spinal cord stimulation (SCS) on the reduction of preimplantation opioid dose and what preimplantation opioid dose is associated with a reduction or discontinuation of opioid use postimplantation. Methods: Systematic review of literature from PubMed, Web of Science, and Ovid Medline search of "opioid" and "pain" and "spinal cord stimulator." Inclusion criteria included original research providing data on SCS preimplantation opioid dosing and 12 months postimplantation opioid dosing or that correlated specific preimplantation opioid dose or opioid dose cutoff with significantly increased likelihood of opioid use discontinuation at 12 months postimplantation. Results: Systematic review of the literature yielded 17 studies providing data on pre-SCS and post-SCS implantation dose and 4 providing data on the preimplantation opioid dose that significantly increased likelihood of opioid use discontinuation at 12 months postimplantation. Data from included studies indicated that SCS is an effective tool in reducing opioid dose from preimplantation levels at 12 months postimplantation. Data preliminarily supports the assertion that initiation of SCS at a preimplantation opioid dose of ≤20 to ≤42.5 morphine milligram equivalents increases the likelihood of postimplantation elimination of opioid use. Discussion: SCS is an effective treatment for many types of chronic pain and can reduce or eliminate chronic opioid use. Preimplantation opioid dose may impact discontinuation of opioid use postimplantation and the effectiveness of SCS in the relief of chronic pain. More research is needed to support and strengthen clinical recommendations for initiation of SCS use at lower daily opioid dose.